Levels of Burnout Among Nurses and Related Factors. - KARA ÖZÇALIK, Cennet; BABAT, Ahmet (Fenerbahce University Journal of Health Sciences (FBU-JOSH) / Fenerbahçe Üniversitesi Sağlık Bilimleri Dergisi, 2025)
Nurses frequently experience challenging emotional situations such as severe illness, poor prognosis, and patient death, and they often work in complex and high-stress work environments. The aim of this study was to examine the levels of burnout and related factors among nurses working in a public hospital. The data of this cross-sectional descriptive study were obtained with the Nurse Information Form and Maslach Burnout Scale between March and April 2023. The comparison of burnout scores was analyzed an with independent sample t-tests for gender, marital status, and voluntary choice of profession; one-way analysis of variance for educational status, total working time in the profession, weekly working time, and working order. The study included 121 participants (≥18 years); the majority were female (66.1%), married (52.1%), and had a bachelor's degree (61.2%). The depersonalization and emotional exhaustion scores of nurses working in specialized units were significantly higher than those of nurses working in inpatient services. The emotional exhaustion and depersonalization scores of nurses with 6-10 years of professional experience were significantly higher than those with 1-5 years of experience. Our findings suggest that nurses may experience more emotional exhaustion and depersonalization when they do not choose the profession willingly and when their professional experience and weekly working hours increase.